Location Based Service for improving Chabot Disaster Management Evacuator Palu - Rohman, Muhammad Syaifur (Jurnal Transformatika, 2020)
The devastating earthquake that struck Palu on the island of Sulawesi last September ripped through the Earth’s crust at a rare high speed, scientists have found. When the disaster is over, many natural disaster victims need immediate help. The call center provided is usually busy with services and complaints from victims of natural disasters. The greater the impact of natural disasters, the more information services that must be carried out. By using CEPAT chatbot for disaster evacuation in Palu, information about evacuation place can be given to victim by access it. Then when the victim shares their location, CEPAT will give the nearest evacuation place information using LBS improvement Chabot.